Broad-range and binary-range acyl-acyl-carrier protein thioesterases suggest an alternative mechanism for medium-chain production in seeds. - Voelker, T A (1997)
In the current model of medium-chain (C8-14) fatty acid biosynthesis in seeds, specialized FatB acyl-acyl-carrier-protein (ACP) thioesterases are responsible for the production of medium chains. We have isolated and characterized FatB cDNAs from the maturing seeds of elm (Ulmus americana) and nutmeg (Myristica fragrans), which accumulate predominantly caprate (10:0)- and myristate (14:0)-containing oils, respectively. In neither species were we able to find cDNAs encoding enzymes specialized for these chain lengths. Nutmeg FatB hydrolyses C14-18 substrates in vitro and expression in Brassica napus seeds leads to an oil enriched in C14-18 saturates. Elm FatB1 displays a binary specificity: one activity is centered on 10:0-ACP, and a second is centered on palmitate (16:0)-ACP. After expression in B. napus seeds the oil is enriched in C10-18 saturates, predominantly 16:0, 14:0, and 10:0. The composition of free fatty acids produced by elm FatB1 in Escherichia coli shifts from C14-16 to mostly C8-10 by increasing the rate of chain termination by this enzyme. These results suggest the existence of an alternative mechanism used in the evolution of medium-chain production, a model of which is presented.